EFFECTIVENESS OF PHYSICAL THERAPY IN IMPROVING THE QUALITY OF LIFE IN CHILDREN WITH CEREBRAL PALSY - Anghel M.; Raţă G. (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2015)
This paper aims to put in highlight that patients with cerebral palsy receiving physical therapy will benefit from an increase in quality of life translated by increasing functional independence. The specific objectives of this study were to assess the child, according to the following dimensions of quality of life: physical and functional well-being and ability to perform normal tasks in their daily existence. To emphasize the need for the study hypotheses we left, according to which if we use therapeutic exercise as a means to educate base / movement re-education, can provide superior traction efficiency indices of function and using means and methods drawn from physical therapy translated can increase quality of life by increasing functional independence. As research methods, we used the theoretical documentation, observation method teaching, methods of exploration and evaluation, statistical and mathematical method, graphical method. The results of the initial and final evaluations were positive upward in terms of quality of life in these children. Findings indicate that specific physical therapy program, applied to children with cerebral palsy contribute to improving quality of life.